Organizational Culture as a Performance Catalyst: An Analysis of its Impact in the Banking Sector of Cirebon - Rahmadan, Nusa; Darmansyah, Panzy; Nurdiana, Editya (Siber International Journal of Digital Business (SIJDB), 2025)
This study investigates the influence of work culture on employee performance in the Cirebon City banking sector. In an era of increasingly fierce competition, a deep understanding of the factors that affect employee performance is essential to improve organizational competitiveness. A work culture that supports collaboration, open communication, inclusive leadership, and a conducive work atmosphere is believed to play a significant role in increasing productivity, work quality, and employee satisfaction. Through a quantitative approach with linear regression methods and correlation analysis, this study found that work culture has a positive and significant influence on employee performance. The results show that improving a positive work culture can improve employee performance in Cirebon City banks, with effective communication and supportive leadership being key factors. These findings provide insights for banking management to strengthen an inclusive and adaptive work culture to improve employee performance and organizational competitiveness.